In vitro susceptibility to 9 antifungal agents of 14 strains of Zygomycetes isolated from clinical specimens - Otcenásek, M; Buchta, V (Mycopathologia, 1994)
Fourteen clinical isolates of Zygomycetes were tested for their in vitro susceptibility to nine antifungal agents. Susceptibility assessment was performed using a microtiter broth dilution method. Synthetic broth with YNB and glucose was used for 5-fluorocytosine and BHI broth for all the other antimycotics. Amphotericin B exhibited the strongest activity against all isolates tested. MIC values of other two polyenes--nystatin and pimaricin--ranged within the susceptibility limits, with a little pronounced higher activity of pimaricin. The isolates of the genus Absidia and Syncephalastrum were well sensitive to all antimycotics with the exception of 5-fluorocytosine and naftifine. A very weak or zero growth inhibitory effect against all members of the genera Mucor and Rhizopus was found in azoles, 5-fluorocytosine and naftifine.
Keywords: Azoles; flucytosin; Microbial Sensitivity Tests; allylamin; Allylamine; mikrobiální testy citlivosti; Flucytosine; Humans; azoly; lidé; Mucorales; Antifungal Agents; Mucor; antifungální látky; Rhizopus